(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
Lara Moreno’s literary work dialogues with the city both in novels and essays. The author presents a series of problems in the urban environment from a critical position, along the lines that the new social novel has been developing over the course of this century. One of the issues dealt with in greater depth is the difficulty of access to housing and the problems derived from this issue: real estate crisis, speculation, social exclusion, urban exodus, gentrification and precariousness, all of which are a direct consequence of neo-capitalism. An issue of this magnitude calls into question the Welfare Society and the validity of certain theories that advocate building a city at the service of the citizen (Lefebvre, Harvey, etc.). Within this framework, in this paper we propose to study the critical content of the novel La ciudad (2022) and the essay Deshabitar (2020) through the prism of the housing problem. We also analyse the author’s narrative proposal and its affiliation with the recently published social novel.